Improved FFT-based alpha-stable density approximation algorithm - BAI Yun; YU Li; ZHU Guang-xi; LI Li (Tongxin xuebao)
Approximation of density of α-stable process is an elementary works in modeling network flow using α-stable process.Combining the mathematical properties of characteristic function of α-stable process with the traditional approximating algorithm,an improved FFT-based algorithm was proposed.The improved algorithm has 2 noticeable features: automatically choosing the sampling space and sampling interval,importing frequency expansion.Experiments show that it can decrease calculation complexity and effectively control computation error.